Calibración de la Máquina de Resistencia a la Abrasión de Adoquines, para su Funcionamiento en el Laboratorio del CIVCO, según Norma Nacional - Jiménez-Venegas, Yeilin (Instituto Tecnológico de Costa Rica, 2009)
The graduation project is divided into 3 main parts, the machine calibration abrasion resistance of paving stones CIVCO lab, based on the technical specifications of the standard INTE 06-02-15-06. The wear of pavement concrete block is made by means of abrasion, comparing CIVCO lab results with the results of Holcim. For future accreditation of testing and the team performed a technical instruction. The test for resistance to abrasion is to place a stone for a body wear through abrasion exerted by a flow of sand that passes tangentially through the cobblestone surface and the lateral side of a metal disc that presses against it , all this is done under controlled conditions. This generates a footprint in the shape of the curved surface of the metal disc. As part of the calibration of the machine abrasion resistance of paving stones, must be verified flux density of abrasive material, this must be constant. For calibration of the reference material, you need the constant flow of abrasive material and place the appropriate counterweight, to produce a footprint of 20 ± 1 mm. Samples were divided by size and color, there were 10 samples for each type. Basic statistics were applied to the results of all tests and drawing a comparison with data from Holcim, all resulting lengths are within the range indicated by the standard (INTE 06-02-15-06). The length of the trace of wear shows a variation with respect to the amount of aggregates that are in cobblestone in the place where the imprint is made.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2009.
Keywords: Longitud de desgaste; Bloque de mármol; Densidad de flujo; Arena de cuarzo; Adoquines de concreto